The Romance of Real Life Charles Brockden Brown and the Origins of American Culture - Watts, Steven, 1952-; Project Muse.; Project Muse. (2019)
The Romance of Real Life shows how a sensitive, prolific writer confronted, wrestled with, and ultimately promoted the emergence of a liberal society in nineteenth-century America.
Watts also shows how Brown's experience was central to broader developments: the rise of the novel in America, the development of gender and family formulations, the clash between republican "virtue" and liberal "self-interest," and the origins of a bourgeois creed of self-control. Perhaps most importantly, he explains how Brown helped articulate a notion of "culture" itself as a civilizing force to restrain restless liberal individualism.
His notoriously volatile private life, it turns out, in many ways flowed from a critique of market society and its impulses.
Offering a revisionist view of Brown himself, Watts examines the major novels of the 1790s as well as previously neglected sources - from early essays and private letters to late-career forays into journalism, political pamphleteering, serial fiction, and cultural criticism. The result is a fuller picture of Brown as a man of letters in post-Revolutionary America, a man who rigorously analyzed the public and private vagaries of individual agency.
Among the leading writers of the early republic, Charles Brockden Brown often appears as a romantic prototype - the brilliant, alienated author rejected by a utilitarian, materialistic American society. In The Romance of Real Life Steven Watts reinterprets Brown's life and work as a complex case study in the emerging culture of capitalism at the dawn of the nineteenth century.
1. The Novel and the Market in the Early Republic -- 2. The Lawyer and the Rhapsodist -- 3. The Young Artist as Social Visionary -- 4. The Major Novels (I): Fiction and Fragmentation -- 5. The Major Novels (II): Deception and Disintegration -- 6. The Writer as Bourgeois Moralist -- 7. The Writer and the Liberal Ego.
Open access edition supported by the National Endowment for the Humanities / Andrew W. Mellon Foundation Humanities Open Book Program.
The text of this book is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License
Includes bibliographical references (pages 225-241) and index.
Description based on print version record.
Keywords: Brown, Charles Brockden; Brown, Charles Brockden, -- 1771-1810.; Brown, Charles Brockden, -- 1771-1810.; Cultuur; Romanticism; Novelists, American; National characteristics, American, in literature; Civilization; Authorship; Authors and readers; Romanticism -- United States; Authorship -- History -- 18th century; Novelists, American -- 18th century -- Biography; National characteristics, American, in literature; Authors and readers -- United States -- History -- 18th century; United States; United States -- Civilization -- 1783-1865.; 1700-1865; United States; English fiction; History; Biographies; Electronic books; Electronic books